DAYA TAHAN ROTAN YANG DIAWETKAN DENGAN CUKA KAYU GALAM TERHADAP SERANGAN BUBUK Dinoderus minutus Farb. - Setiawati, Evy (Jurnal Riset Industri Hasil Hutan, 2010)
Rattan on frequently attacked by the powder post beetle (Tellu, 2001). The prevention of dry powder attacks is done by preservation. The increasing resistant of rattan from insect attack can be done by an environmentally friendly preservative, the Galam wood vinegar. This research  aims to determine the most effective concentration of preservative that shows the lowest attacks level of D. Farb minutus powder. The rattan used is green rattan (Calamus sp.) The concentration of preservative that are used:10%, 40%, 70% and 100%. The testing of dry powder attack  used force feedback method. The effectiveness test parameters of wood vinegar to dry powder attacks  included degree of protection Dinoderus minutus Farb. powder,  reduction percentage of rattan weight and the mortality of dry powder Dinoderus sp for toxicological testing of wood vinegar. The test results showed that the degree of protection powder in rattan growing along with the increased concentration of preservatives. The higher the concentration of  wood vinegar, the smaller the reduction of rattan weight and the higher the mortality rate of dry powder. Keywords: resistant of rattan, wood vinegar, Dinoderus minutus.